Distribution of spring phytoplankton (mainly diatoms) in the upper 50 m of the Southwestern Atlantic Ocean (30-61°S) - Olguín, H.F. (2006)
This is the first study on diatom spatial patterns in relation to major oceanographic features along a megascale transect in the Southwestern Atlantic Ocean and provides a comparison with diatom distribution in surface sediments. Absolute abundances of diatoms, silicoflagellates and dinoflagellates (>10-μm fraction) were assessed in 80 bottle samples from 5 to 50 m, retrieved in November 1993 at 20 stations (30-61°S) along 53°W. Siliceous phytoplankton were scarce in the northern half of the transect and in the south of 57°S (100-150 cells L-1), with a strong peak in the vicinity of the Polar Front (∼200 000 cells L-1), whereas dinoflagellates were more abundant at the northern stations (up to 24 000 cells L-1). In the south of 50°S phytoplanktonic cell densities were loosely (but significantly, r = 0.54, P < 0.01) associated with chlorophyll a, whereas in the north of this latitude, this relationship disappeared (r = 0.018, P > 0.1). In total, 191 diatoms and 4 silicoflagellates were recorded. Changes in diatom assemblage compositions along the transect allowed identification of five discrete areas: Subtropical (29°S), Northern Transitional (34-41°S), Southern Transitional (43-48°S), Subantarctic (49-54°S) and Antarctic (55-59°S), each characterized by a set of typical species. Diversity changed little with latitude, but numbers of species were higher in the north of 40°S. Comparison of diatom assemblage makeup in the plankton and in the surface sediments shows very strong disagreements, whereby cold water species are very significantly over-represented in the sedimentary record, suggesting enhanced preservation and strong subsurface equatorward advection of the cold water taxa. © The Author 2006. Published by Oxford University Press. All rights reserved.